Case Report: Development of severe inflammatory orbitopathy after immune checkpoint inhibitor initiation - Madala, Samantha; Parikh, Alomi; Hong, Kendra; Burnstine, Michael (Frontiers in Ophthalmology, 2025)
We report a case of thyroid eye disease (TED) reactivation, review the literature, and raise awareness of severe ophthalmopathy and myositis following the initiation of cancer treatment with an immune checkpoint inhibitor (ICI). In this case, after starting nivolumab, a 68-year-old woman with a past medical history of stage 2C uterine carcinoma status post-hysterectomy and past ocular history of thyroid eye disease developed ophthalmoplegia, proptosis, decreased color vision, optic disc hemorrhage, and ocular inflammation. Halting nivolumab and starting 2 weeks of intravenous steroids, one dose of teprotumumab, and low-dose orbital radiation resulted in an improvement in her orbitopathy. ICIs have become popular in oncologic treatment regimens, but they can have serious adverse effects including thyroiditis, Hashimoto’s hypothyroidism, or Graves’ disease complicated by TED. Multiple cases have been reported in the literature of both the reactivation of TED and the presentation of a TED-like orbital inflammation, which we summarize here. Awareness of orbital inflammation due to ICI use is critical, and ICIs should be used with caution in patients with a history of thyroid disease due to the risk of TED reactivation.